A 2-Year Cost Analysis of Maximum Nonoperative Treatments in Patients With Symptomatic Lumbar Stenosis or Spondylolisthesis That Ultimately Required Surgery. Issue 4 (June 2019) - Adogwa, Owoicho; Davison, Mark A.; Lilly, Daniel T.; Vuong, Victoria D.; Desai, Shyam A.; Moreno, Jessica; Cheng, Joseph; Bagley, Carlos
Study Design: Retrospective cohort study. Objectives: The purpose of this study is to characterize the utilization and costs of maximal nonoperative therapies (MNTs) within 2 years prior to spinal fusion surgery in patients with symptomatic lumbar stenosis or spondylolisthesis. Methods: A large insurance database was queried for patients with symptomatic lumbar stenosis or spondylolisthesis undergoing index 1-, 2-, or 3-level lumbar decompression and fusion procedures between 2007 and 2016. This database consists of 20.9 million covered lives and includes private/commercially insured and Medicare Advantage beneficiaries. The utilization of MNTs within 2 years prior to index surgery was assessed by cost billed to the patient, prescriptions written, and number of units billed. Results: A total of 27 877 out of 3 423 114 (0.8%) eligible patients underwent posterior lumbar instrumented fusion. Patient MNT utilization was as follows: 11 383 (40.8%) used nonsteroidal anti-inflammatory drugs (NSAIDs), 19 770 (70.9%) used opioids, 12 414 (44.5%) used muscle relaxants, 14 422 (51.7%) received lumbar epidural steroid injection (LESI), 11 156 (40.0%) attended physical therapy/occupational therapy, 4005 (14.4%) presented to the emergency department, and 4042 (14.5%) received chiropractor treatments. The total direct cost associated with all MNTs prior to index spinal fusion was $28 241 320 ($1013.07 per/patient). LESI comprised the largest portion of the total cost of MNT ($15 296 941, 54.2%), followed by opioids ($3 702 463, 13.1%) and NSAIDs ($3 058 335, 10.8%). Conclusions: Opioids are the most frequently prescribed and most used therapy in the preoperative period. Assuming minimal improvement in pain and functional disability after maximum nonoperative therapies, the incremental cost effectiveness ratio for MNT could be highly unfavorable.